Overexpression of a Neural-specific Rho Family GTPase, cRac1B, Selectively Induces Enhanced Neuritogenesis and Neurite Branching in Primary Neurons - Albertinazzi, Chiara (The Rockefeller University Press, 1998)
Rho family GTPases have been implicated in cytoskeletal reorganization during neuritogenesis. We have recently identified a new gene of this family, cRac1B, specifically expressed in the chicken developing nervous system. This GTPase was overexpressed in primary neurons to study the role of cRac1B in the development of the neuronal phenotype. Overexpression of cRac1B induced an increment in the number of neurites per neuron, and dramatically increased neurite branching, whereas overexpression of the highly related and ubiquitous cRac1A GTPase did not evidently affect neuronal morphology. Furthermore, expression of an inactive form of cRac1B strikingly inhibited neurite formation. The specificity of cRac1B action observed in neurons was not observed in fibroblasts, where both GTPases produced similar effects on cell morphology and actin organization, indicating the existence of a cell type-dependent specificity of cRac1B function. Molecular dissection of cRac1B function by analysis of the effects of chimeric cRac1A/cRac1B proteins showed that the COOH-terminal portion of cRac1B is essential to induce increased neuritogenesis and neurite branching. Considering the distinctive regulation of cRac1B expression during neural development, our data strongly support an important role of cRac1B during neuritogenesis, and they uncover new mechanisms underlying the functional specificity of distinct Rho family GTPases.